Efficient Electrochemical Production of Syngas from CO2 and H2O by using a Nanostructured Ag/g‐C3N4 Catalyst. Issue 9 (19th July 2016) - Sastre, Francesc; Muñoz‐Batista, Mario J.; Kubacka, Anna; Fernández‐García, Marcos; Smith, Wilson A.; Kapteijn, Freek; Makkee, Michiel; Gascon, Jorge
Abstract: A new series of electrocatalysts consisting of Ag nanoparticles supported on graphitic carbon nitride (g‐C3 N4 ) are presented. The combination of nanostructured silver and a carbon nitride support results in the direct generation of synthesis gas (CO+H2 ) during the electrocatalytic reduction of CO2 in water. By using a state‐of‐the‐art electrocatalytic setup, the influence of different operation parameters over the final product composition is shown. The H2 /CO product ratio can easily be tuned from 100:1 to 2:1 with high reproducibility by controlling the applied potential and the Ag loading. More importantly, long‐term and catalyst reuse experiments demonstrate the robustness of these electrodes, which could be operated for over 20 h time on stream and reused several times without any evident loss of activity or selectivity. Our results highlight the potential of nanostructuring Ag‐based catalysts and the relevance of the selected support for the green valorization of CO2 . Abstract : Moral support : A new catalytic system consisting of Ag nanoparticles supported over graphitic carbon nitride (g‐C3 N4 ) is reported. By controlling the applied potential and the Ag loading, the H2 /CO ratio can easily be tuned from 100:1 to 2:1 with high reproducibility and outstanding stable productivity.